Women's experiences with enhanced recovery after elective caesarean section with next day discharge: A qualitative study. (April 2020) - Cusack, Lynette; Digenis, Christianna; Schultz, Tim; Klaer, Bronwen; Hobbs, Meredith
Abstract: Background: A maternity service in Australia recently implemented an 'Enhanced recovery after Elective Caesarean' pathway, which includes antenatal preparation and facilitates an active role in postnatal recovery such as encouraging mobility and early cessation of fasting. The pathway includes next day discharge for women and their babies after elective caesarean section and safely transitions maternity care from hospital to home with community midwifery care. While enhanced recovery has been implemented in a number of surgical procedures to reduce hospital stay and to improve patient outcomes it has only been considered for elective caesarean sections in more recent years. Given this, enhanced recovery is not well established or researched in obstetric contexts. Furthermore, women's experiences with reduced hospital stays post-caesarean, particularly next day discharge, is limited. A qualitative explorative descriptive study of women's experiences with the pathway and the associated early transition home will help to inform clinical practice and the research evidence base. Methods: Eleven interviews were conducted with women who had experienced the pathway and next day discharge. Thematic analysis was conducted. Findings: Three major themes and twelve sub-themes emerged from the data. Major themes identified were women's general experience of an enhanced recovery pathway, their experiences following arrival at home and support at home. All women interviewed were satisfied with the pathway and home recovery. However, there are a number of aspects of care that are essential to a positive experience. This includes excellent support from social networks, healthcare staff and home midwifery care; well managed pain relief; and adequate and timely information, including reassurance that they or their baby could remain in hospital if required. Conclusion: This study takes a woman-centred perspective adding to both literature and practice.